Hubungan Komunikasi Terapeutik Perawat Dengan Kepuasan Keluarga Orang Dengan Gangguan Jiwa di UPTD Rumah Sakit Jiwa Prof.Dr. V. L. Ratumbuysang - Peginusa, Gloria Makahanap; Kairupan , Bernabas Harold Ralph; Bidjuni, Hendro (Mapalus Nursing Science Journal, 2023)
Mental disorders are currently experiencing a very significant increase, every year in various parts of the world the number of people with mental disorders increases. One of the efforts to increase patient and family satisfaction by implementing nurse therapeutic communication during patient care in the hospital. The aim is to determine the relationship between Nurse therapeutic communication with Family Satisfaction who have family members with mental disorders at Mental Hospital Prof. Dr. V. L. Ratumbuysang. This method uses descriptive research with survey methods. The sample amounted to 123 respondents obtained using the Total Sampling technique. The results of statistical tests using the Chi-square test at a significance level of 95%, obtained a significant value of ρ = 0.000 < α (0.05) The conclusion there is a relationship between Nurse's therapeutic communication with Family Satisfaction who have Mental disorders increases family members at Mental Hospital Prof. Dr. V. L. Ratumbuysang. Suggestions are expected for health service providers to continue to provide services by prioritizing patient and family satisfaction by conducting therapeutic communication. Keywords: Nurses; Therapeutic Communication; Family Satisfaction; Mental Disorders